A critical analysis of the Delay Rule in South African Administrative Law post State Information Technology Agency Soc Limited v Gijima Holdings (PTY) Limited - Basini-Gxokonyeka, Nosicelo Natasha (Department of Public Law, 2023)
The State Information Technology Agency's (SOC) Limited v Gijima Holdings (Pty) Ltd was seminal in establishing that the Promotion of Administrative Justice Act, 2000 is not available to an organ of state wishing to set aside its own decision while acting in its own interest. The case is also significant for the impact it has had on the delay rule. This paper identifies a problem presented by what will be referred to as the Gijima principle. The principle suggests that a court may be required to declare a decision unconstitutional in accordance with section 172(1)(a) of the Constitution even if there is no basis for overlooking the unreasonableness of the delay. This paper considers the impact of the Gijima judgement on the delay rule and the continued relevance of the delay rule in administrative law post- Gijima. It will be argued that there are three major challenges this principle poses to the rule of law namely, it promotes arbitrary and opportunistic self-serving reviews by state officials. Secondly, it indirectly promotes disregard of public procurement laws by making it easy for organs of state to undo their decisions. Lastly, it undermines the finality and certainty of decisions, which have the potential to deter prospective suppliers from contracting with the state. This paper critically assesses trends emerging from lower courts in response to the Gijima principle and provides recommendations as to how some of the issues raised by the judgment's approach may be rectified. Overall, I argue that the Gijima principle effectively eradicates the delay rule and that there is a need for continued relevance of the rule in administrative law. The Constitutional Court needs to strike a balance between preserving the delay rule on the one hand and exercising its prerogative to develop the common law on the other.